Appeals and spiels: a comparative analysis on alcohol advertising in the USA and Ireland. (2018) - Gibic, Amina; Natarajan, Vivek S.; Sen, Kabir Chandra
The USA and Ireland vary in their policies and regulations regarding the alcohol industry. In this study, we sought to see whether the consumption of alcoholic beverages, and alcohol company's appeals and target audiences varied among the two countries, as well. 150 total alcohol commercials (75 from the USA, 75 from Ireland), ranging from the year 2002 to the current year, were collected and analysed. The brand, commercial name, appeal used (image, product, sex or humour), type of alcoholic beverage promoted, and the audience targeted (young men ages 18-49, young women ages 18-49 and niche markets: craft beer, health conscious, sports fans) were observed and noted, as were ads explicitly targeting youth. Although appeal utilised and type of alcoholic beverage promoted did not vary significantly between the two countries, the target audiences by country varied significantly, as did target audience by type of alcoholic beverage. This study reveals how the similarities in alcohol advertisements contrast with the difference in policies and regulations among the USA and Ireland, thus bringing the varying levels of industry clout and influence between the two countries to light.